ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Dr. Jipsy Malhotra, Dr. Priyanka S. Niranjan (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2014)
Artificial Intelligence is a rising technological discipline which holds the potential to change every feature of our lives. In the education sector, Artificial Intelligence has helped in introducing novel classroom techniques that are now undergoing testing in different domains. This paper discusses how application of AI has become a game changer for stakeholders in education, particularly in developing countries, like India. This paper analyses the role of AI in improving the teaching learning process in different subjects and how it enables us to achieve desirable outcomes. The aim is to focus on the productive side of using Artificial Intelligence in school platform and understand the competitions and ways related to it. Keywords: Artificial intelligence, education, school, teaching process, E-learning, innovation and technology.